A factual assessment of the Draft Common Frame of Reference - Antoniolli, Luisa; Fiorentini, Francesca (Sellier, 2011)
This book contains a case-based assessment of the Draft Common Frame of Reference carried out by the Common Core Evaluating Group, which gathers a number of well-established and younger scholars coming from Eastern and Western countries of the European Union using the working method of the research project ‘The Common Core of European Private Law’ (www.common-core.org). The aim of the assessment is to test how the Draft Common Frame of Reference could work when applied in different national legal systems. To this end, a number of factual situations, i.e. hypothetical cases, have been drafted by the authors and solved through the application of both national rules and rules of the DCFR. Thereby, similarities and differences in the outcome of the cases have been analysed, together with difficulties - if any - in the application of the ‘Principles of European Law’. The Common Core assessment has been carried out as part of the ‘Joint Network of European Private Law’ Project (CoPECL), financed by the EU Commission.